Promoting Open Science Principles and Primenjena psihologija (Applied Psychology) - Mellor, David; Pajić, Dejan (Primenjena psihologija, 2023)
At its heart, “open science” is a simple matter of sharing key parts of the research process that are traditionally not shared. These include detailed methods, protocols, and other materials needed to conduct the work: detailed analytical steps or code used for data analysis, the raw data collected during an investigation, and preliminary drafts of the manuscript. A default towards not sharing may be for many reasons, but for many years, the largest reason is that it was simply not possible to share raw data before online publication became the standard. That status quo became embedded in lab culture, and simply changing the status quo in a community as decentralized as the scientific community is always going to be a slow process. The fact that sharing more details about the process of scientific research represents a possible risk for the researcher, in a system where only statistically significant findings are publishable (Dickersin 1990; Komukai, Sugita, and Fujimoto 2023) and where others are not required to share their materials, makes it all the more challenging to move beyond the current state. By presenting activities at the Center of Open Science and efforts by the Primenjena psihologija editorial board, we appeal to our readers and fellow researchers to embrace the open science practice and use the examples provided in this special issue as a guidance for their future scientific endeavors.